(untitled) (Gragoatá, 2018)
Ahmadou Kourouma’s Allah is Not Obliged is a fiction based on the civil wars in the West African countries of Liberia and Sierra Leone as a result of the breakdown of democracy. It employs the point of view of a child narrator, Birahima, a literalist picaro, to narrate wartime atrocities. The novel, mainly a satire, employs the devices of irony and humour that allow Birahima to present his world, which is turned upside down, and morality, reversed, in a way that makes the reader laugh in spite of the horror. The reality of Birahima’s wartime experience, which has left him in a kind of developmental “limbo”, is difficult to believe to be true. However, he makes every effort in his use of language to prove the truthfulness of the absurdity he narrates. This paper considers how the protagonist/narrator Birahima’s entry into war leaves him in an absurd, cyclical limbo while he resorts in frustration to validate his absurd experience through appealing to God, folk wisdom and dictionaries. ———————————————————————————— “WALAHÉ!”; “VOCÊ TINHA QUE TER VISTO”: VALIDANDO A VERDADE DOS ABSURDOS DA GUERRA EM ALLAH IS NOT OBLIGED, DE AHMADOU KOUROUMA Allah is Not Obliged, de Ahmadou Kourouma, é uma obra de ficção baseada nas guerras civis nos países da África Ocidental Libéria e Serra Leoa resultantes do colapso da democracia. Através do ponto de vista de um narrador infantil, Birahima, um pícaro literalista, a obra narra as atrocidades da guerra. O romance, essencialmente uma sátira, emprega os recursos da ironia e do humor para permitir que Birahima apresente seu mundo deturpado e sua moralidade invertida de uma maneira que faz o leitor rir apesar do horror. É difícil aceitar como verdade a realidade que Birahima vivenciou na guerra, que deixou o seu desenvolvimento em uma espécie de limbo. No entanto, ele se utiliza da linguagem ao máximo para provar a veracidade do absurdo que ele narra. Este artigo considera como a entrada do protagonista / narrador Birahima na guerra o deixa em um limbo cíclico e absurdo, enquanto ele se frustra para validar sua experiência absurda apelando a Deus, à sabedoria popular e aos dicionários. — Artigo em inglês. — DOI: http://dx.doi.org/10.22409/gragoata.2018n45a1097.